2012
DOI: 10.1387/ijdb.120009nd
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the eukaryotic initiation factor 6 and kermit2/gipc2 in Xenopus laevis pronephros formation

Abstract: The translation initiation factor Eif6 has been implicated as a regulator of ribosome assembly, selective mRNA translation and apoptosis. Many of these activities depend upon the phosphorylation of eif6 Serine 235 by protein kinase C (PKC). Eif6-60S is probably part of the RNAinduced silencing complex (RISC). eif6 over-expression in Xenopus embryos causes aberrant eye development. kermit2/gipc2 morphants have an eye phenotype similar to that of the eif6 overexpressors. Eye formation is regulated by insulin gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Frozen 10 μm-thick sections were obtained after embedding and freezing liver fragments in Killik (Bio Optica, Milan, Italy). Sections were then stained with hematoxylin-eosin and mounted in PBS/glycerol (9:1, v/v) (Tussellino et al, 2012 ; Alwahsh et al, 2014 ). Sections were photographed with a Leica CTR 6500 UV microscope (Leica Microsystems CMS gmbH, Wetzlar, Germany) and degree of steatosis was evaluated by ImageJ software.…”
Section: Methodsmentioning
confidence: 99%
“…Frozen 10 μm-thick sections were obtained after embedding and freezing liver fragments in Killik (Bio Optica, Milan, Italy). Sections were then stained with hematoxylin-eosin and mounted in PBS/glycerol (9:1, v/v) (Tussellino et al, 2012 ; Alwahsh et al, 2014 ). Sections were photographed with a Leica CTR 6500 UV microscope (Leica Microsystems CMS gmbH, Wetzlar, Germany) and degree of steatosis was evaluated by ImageJ software.…”
Section: Methodsmentioning
confidence: 99%
“…The ability of eif6 to control gipc2 expression is active also in the case of pronephros development, where eif6 overexpression causes edema and damage of the three main components of the pronephros. gipc2 depletion induces the edema phenotype and reduction of the pronephros constituents, as indicated by several markers, such as lhx 1 and nephrin [ 8 ]. Moreover, p110*, a constitutively active p110 subunit of pi3 kinase, corrects the abnormal kidney phenotype induced by eif6, suggesting that, similarly to the eye, eif6 may control the expression of gipc2, which is essential for pronephros morphogenesis and dependent on igf-induced akt activation [ 8 ].…”
Section: Xenopus In Developmental Studiesmentioning
confidence: 99%
“…This means that no approval from the health authorities is needed for in vivo experiments that involve the early stages of this species. Among the great advantages of Xenopus , there is its evolutionary closeness to higher vertebrates in terms of physiology, gene expression and organ development, such as the eyes, liver, lungs, heart, kidney and so on, thus allowing the transfer of the results directly to the human species [ 7 , 8 , 9 , 10 , 11 , 12 ]. In recent years, this model of animal species has gradually attracted the attention of ecotoxicologists and been applied in studies relating to ecotoxicology.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, GIPC2 is expressed in certain glands, such as breast, adrenal, salivary and thyroid glands (10). Previous studies have demonstrated an important role for GIPC2 in embryonic development (11,12) and the occurrence of digestive tract tumors (13,14); however, the role of GIPC2 in COAD has yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%